Himmel und Hölle - Orte des Gerichts und der Rettung - Feldmeier, Reinhard (Evangelische Theologie, 2023)
Time and again religions have played a calamitous role in political conflicts. The statements of the Moscow Patriarch Cyril on Putin's war exemplarily show that Christianity can't wash its hands in innocence either. Therefore, the widespread desire to abolish "heaven" and "hell", i.e., the division of humanity into the saved and the damned is only too understandable. If in the following contribution religion is nevertheless defended - including the idea of an "afterlife" and a divine judgment - it is done in clear awareness of the possible abuse of these topoi from black pedagogy to terrorism.